Fabrication of PEGylated porphyrin/reduced graphene oxide/doxorubicin nanoplatform for tumour combination therapy. Issue 9 (29th March 2021) - Ma, Weiqian; Yang, Huailin; Hu, Yanfang; Chen, Li
Abstract: In cancer treatment, combination therapy has been considered as an attractive strategy to lower side effects and enhance therapeutic efficacy. Herein, we fabricated a kind of reduced‐graphene‐oxide‐based drug delivery system for combination therapy, in which reduced graphene oxide (rGO) as photothermal agent and drug carrier was modified by PEGylated (PEG, polyethylene glycol) tetrahydroxyphenyl porphyrin (THPPEG) via a π–π stacking interaction. The obtained rGO/THPPEG not only showed good biocompatibility and water solubility, but also realized the combination of photothermal therapy with photodynamic therapy. The rGO/THPPEG nanoparticles with stable nanosize were demonstrated by Fourier transform infrared spectroscopy, Raman spectroscopy, TGA, X‐ray photoelectron spectroscopy, TEM images and dynamic light scattering. To verify the feasibility of delivering drugs, doxorubicin (DOX) was chosen to prepare rGO/THPPEG/DOX, realizing synergetic photothermal/photodynamic/chemotherapy. The data of in vitro experiments indicated that rGO/THPPEG/DOX could obviously inhibit tumour growth, outlining the significant potential for future cancer treatment. © 2021 Society of Industrial Chemistry. Abstract : Herein, a kind of PEGylated porphyrin/reduced‐graphene‐oxide‐based drug delivery system was fabricated for combination therapy.